Partial human Janus kinase 1 deficiency predominantly impairs responses to interferon gamma and intracellular control of mycobacteria - Daza-Cajigal, Vanessa; Albuquerque, Adriana S.; Young, Dan F.; Ciancanelli, Michael J.; Moulding, Dale; Angulo, Ivan; Jeanne-Julien, Valentine; Rosain, Jérémie; Minskaia, Ekaterina; Casanova, Jean-Laurent; Boisson-Dupuis, Stéphanie; Bustamante, Jacinta; et al. (Frontiers in Immunology, 2022)
Purpose: Janus kinase-1 (JAK1) tyrosine kinase mediates signaling from multiple cytokine receptors, including interferon alpha/beta and gamma (IFN-α/β and IFN-γ), which are important for viral and mycobacterial protection respectively. We previously reported autosomal recessive (AR) hypomorphic JAK1 mutations in a patient with recurrent atypical mycobacterial infections and relatively minor viral infections. This study tests the impact of partial JAK1 deficiency on cellular responses to IFNs and pathogen control. Methods: We investigated the role of partial JAK1 deficiency using patient cells and cell models generated with lentiviral vectors expressing shRNA. Results: Partial JAK1 deficiency impairs IFN-γ-dependent responses in multiple cell types including THP-1 macrophages, Epstein-Barr Virus (EBV)-transformed B cells and primary dermal fibroblasts. In THP-1 myeloid cells, partial JAK1 deficiency reduced phagosome acidification and apoptosis and resulted in defective control of mycobacterial infection with enhanced intracellular survival. Although both EBV-B cells and primary dermal fibroblasts with partial JAK1 deficiency demonstrate reduced IFN-α responses, control of viral infection was impaired only in patient EBV-B cells and surprisingly intact in patient primary dermal fibroblasts. Conclusion: Our data suggests that partial JAK1 deficiency predominantly affects susceptibility to mycobacterial infection through impact on the IFN-γ responsive pathway in myeloid cells. Susceptibility to viral infections as a result of reduced IFN-α responses is variable depending on cell type. Description of additional patients with inherited JAK1 deficiency will further clarify the spectrum of bacterial and viral susceptibility in this condition. Our results have broader relevance for anticipating infectious complications from the increasing use of selective JAK1 inhibitors.